Hematopoietic stem cells: can old cells learn new tricks? - Ho, Anthony Dick; Punzel, Michael (Journal of leukocyte biology, 2003)
Since the establishment of cell lines derived from human embryonic stem (ES) cells, it has been speculated that out of such “raw material,” we could some day produce all sorts of replacement parts for the human body. Human pluripotent stem cells can be isolated from embryonic, fetal, or adult tissues. Enormous self-renewal capacity and developmental potential are the characteristics of ES cells. Somatic stem cells, especially those derived from hematopoietic tissues, have also been reported to exhibit developmental potential heretofore not considered possible. The initial evidences for the plasticity potential of somatic stem cells were so encouraging that the opponents of ES cell research used them as arguments for restricting ES cell research. In the past months, however, critical issues have been raised challenging the validity and the interpretation of the initial data. Whereas hematopoietic stem-cell therapy has been a clinical reality for almost 40 years, there is still a long way to go in basic research before novel therapy strategies with stem cells as replacement for other organ systems can be established. Given the present status, we should keep all options open for research in ES cells and adult stem cells to appreciate the complexity of their differentiation pathways and the relative merits of various types of stem cells for regenerative medicine.
Gesehen am 10.12.2021